Invisible Bactericidal Coatings on Generic Surfaces through a Convenient Hand Spray - Valinton, Joey Andrew A (Langmuir : the ACS journal of surfaces and colloids, 2022)
Robust antimicrobial coatings featuring high transparency, strong bactericidal activity, and an easy application procedure on generic surfaces can be widely accepted by the public to prevent pandemics. In this work, we demonstrated the hand-sprayer-based approach to deposit complex oxide coatings composed of Co-Mn-Cu-Zn-Ag on screen protectors of smartphones through acidic redox-assisted deposition (ARD). The as-obtained coatings possess high transparency (99.74% transmittance at 550 nm) and long-lasting durability against swiping (for 135 days of average use) or wet cleaning (for a routine of 3 times/day for 33 days). The spray coating enabling 3.14% Escherichia coli viability can further be reduced to 0.21% through a consistent elemental composition achieved via the immersion method. The high intake of Cu2+ in the coating is majorly responsible for the bactericidal activity, and the presence of Ag+ and Zn2+ is necessary to achieve almost complete eradication. The success of extending the bactericidal coatings on other typical hand-touched surfaces (e.g., stainless steel railings, rubber handrails, and plastic switches) in public areas has been demonstrated